CONTACT IMPROVISATION, A DANCE TECHNIQUE AS A REPRESENTATIVE ART FORM OF THE SEVENTIES IN AMERICAN CULTURE - Tafferner-Gulyas, Viktoria (European Scientific Journal, ESJ, 2015)
My research paper intends to examine a dance technique – Contact Improvisation - founded by Steve Paxton in the early-seventies as an art event that was supposed to display the body‘s natural ability to respond physically to the effects of its environment. I would like to explore to what extent Contact Improvisation as an art form is a good representation of the phenomena of the 1970s in American Society. I will look at this dance technique from multiple different aspects, those that could be considered as characteristics of the seventies. These are some of the ideas I elaborate in my conference paper: i. I will research whether the broad, almost nationwide interest in the experience of spiritual rebirth and transcendentalism can be experienced behind the ideas that Contact Improvisation represents. ii. I will try to reveal how this technique worked against the general alienated feeling of the ‘Me Decade‘ because we know that Steve Paxton – initiator of this technique - insisted on Contact Improvisation as a group work, creating deep bonds. iii. The seventies were famous for their solid base for consciousness raising movements. Freeing the body and its sexuality from the earlier social control opened the door to body expressions that had previously repressed. I will argue that Contact Improvisation works as a tool of exploring the natural capabilities and possibilities of the human body as a new frontier and let participants feel equal in the interaction. iv. I would like to discuss the connection between Contact Imrovisation and the decline of American institutions in the seventies as Contact Improvisation is emphasized to be non-hierarchical and egalitarian.